Analisis Pengaruh Nilai Tambah Ekomoni dan Nilai Tambah Pasar terhadap Harga Saham pada Perusahaan Sektor Ritel yang Listing di BEI - MARDIYANTO, HERRY (Jurnal Ilmu Manajemen (JIM), 2013)
The company performance is a parameter tool of management success in managing the company's resources. This study aimed to determine the effect of the Economic Value Added (EVA) and Market Value Added (MVA) to the stock price. Sampling was done by purposive sampling method with a total sample 7 retail companies listed in Indonesia Stock Exchange 2006-2011. Hypothesis test is using multiple regression analysis. The results showed that both variables simultaneously EVA and MVA influence on stock prices. While the MVA only partially affecting stock prices. MVA influence on stock prices because the stock price is affected by market information. While EVA has no effect on stock prices as Value Capital Charge higher than NOPAT shows that the company debts are high. Keywords: economic value added, market value added and stock prices.